2021
DOI: 10.3390/su14010257
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Non-Conventional Irrigation Water in Greenhouse Cucumber (Cucumis sativus) Production

Abstract: Climate change, urbanization and subsequent environmental changes are depleting freshwater resources around the globe. The reuse of domestic, industrial and agricultural wastewater is an alternative approach to freshwater that can be used for irrigation purposes. However, these wastewaters may contain hazardous and toxic elements, such as heavy metals that are hazardous for human health and the environment. Therefore, an experiment was conducted to evaluate the concentration of macro, micro and heavy metals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Nitrogen application augments proline, GB and synthesis of soluble sugars, which in turn ensure the essential nutrients (P, K, Zn, Fe, B and Mn etc) uptake under saline conditions (Perveen et al, 2016;Hossain et al, 2020). The adequate nitrogen supply in saline soil regulates plasma membrane activity and maintain membrane stability indices confer the reduced negative effect of salinity and continues intake of nutrient from saline stressed soil (Khan et al, 2013;Singh et al, 2014;Parihar et al, 2015;Hossain et al, 2020;Kumar et al, 2021;Kumari et al, 2022).…”
Section: N-mediated Maintenance Of Nutrient Balancementioning
confidence: 99%
“…Nitrogen application augments proline, GB and synthesis of soluble sugars, which in turn ensure the essential nutrients (P, K, Zn, Fe, B and Mn etc) uptake under saline conditions (Perveen et al, 2016;Hossain et al, 2020). The adequate nitrogen supply in saline soil regulates plasma membrane activity and maintain membrane stability indices confer the reduced negative effect of salinity and continues intake of nutrient from saline stressed soil (Khan et al, 2013;Singh et al, 2014;Parihar et al, 2015;Hossain et al, 2020;Kumar et al, 2021;Kumari et al, 2022).…”
Section: N-mediated Maintenance Of Nutrient Balancementioning
confidence: 99%
“…Another important physiological parameter is water potential because it is used for determining the water status of the plants [46]. Khan and coworker did the experiments in Cucumis sativa, the result showed that the water potential decreased linearly with increasing salinity levels [47]. In another experiment, Romero and coworker demonstrated water uptake and water relationships under saline growing conditions in the tomato (Lycopersicon esculentum) cultivars.…”
Section: Effect Of Salt Stress On Physiological Responsesmentioning
confidence: 99%